CRITICAL SUCCESS FACTORS AFFECTING QUALITY, COST AND TIME CONTROL IN CONSTRUCTION PROJECTS - SAMSURI, AIN SYAFINAZ (Universiti Teknologi PETRONAS, 2017)
To date, the clients of the construction industry are primarily concerned with quality, time and cost. The majority of construction projects are obtained on the basis of just two of these parameters, in particular time and cost. In order to plan and manage a successful project, the three parameters of time, cost and quality ought to be considered. For time, timely completion of a construction project is often seen as a major criterion of project success by clients, contractors and consultants alike. They announced that the industry will transform by 2020 by improving its quality, safety, environmental sustainability and productivity. This action highlights the importance of quality, cost and time control in construction and acknowledging it as one of the critical factors in successful construction project completion. Construction projects are constantly anticipated to create a balance between cost, time and quality. It is possible to have high quality and low cost, however at the expense of time, and conversely to have high quality and a fast project, but at a cost. High quality is not generally the essential target for the client; however, it is critical to gain a successful project.